Website-Based Government Learning Development: An Innovation for Learning in the Implementation of Life-Based Curriculum - Untari, Sri; Saputra, Meidi; Taufiqurrahman, Muhammad (International Journal of Interactive Mobile Technologies (iJIM), 2022)
In the digital era, the internet is one of the most influential learning resources in various sectors including the education sector. With the digitalization process in the education sector, the learning process can be carried out anywhere and anytime, the concept of "space and time" which has been an indicator in determining the speed and understanding of students begins to fuse with digital learning in the form of virtual learning, this is in line with the concept of a life-based curriculum which emphasizes that the learning process can be carried out anywhere, in any situation and circumstance. This study aims to develop a website-based government learning product as a learning innovation in the implementation of a life-based curriculum. The specific objectives of this study are (1) how the characteristics of the development of website-based government learning are, and (2) how effective the development of website-based government learning is. The development is carried out using the development model from Sugiyono (2013) which has been adjusted by the researcher. The product of the learning model was then tested for validity and product testing with students majoring in Law and Citizenship at the State University of Malang as test respondents . Please add with research result